Developing Empathetic Preservice Teachers Using Literary Fiction - David Wolff (The Advocate, 2025)
This purpose of this research focuses on the use of literary fiction as case studies to develop empathy with preservice teachers in a teacher education program using the Scholarship of Teaching and Learning. Empathy, defined in three manners as cognitive empathy, emotional empathy, and compassionate empathy, is an essential attribute of educators. Not all preservice teachers have similar experiences as their students and need opportunities to develop empathy. This article includes personal reflections over two-years of teaching literacy methods and represents the researcher’s learnings as they aim to position preservice teachers to empathize with students with dyslexia. The instructional journey of the researcher is discussed including the use of three literary fiction to cause preservice teachers to consider the perspectives of three protagonists living and learning with dyslexia. As a result, four themes emerged from the researcher’s observations describing what the preservice teachers learned: holistic, genuine, perception, and professionalism.
Keywords: teacher education; empathy; literary fiction; dyslexia; science of reading; Scholarship of Teaching and Learning